Intravenous versus subcutaneous tocilizumab in Takayasu arteritis: multicentre retrospective study - Patrice Cacoub; Arsène Mekinian; David Saadoun; Pavel I Novikov; Savino Sciascia; Corrado Campochiaro; Olivier Fain; Ilya Smitienko; Nicolas Schleinitz; Patrick Jégo; Francesco Muratore; Carlo Salvarani; et al. (RMD Open)
Objectives In this large multicentre study, we compared the effectiveness and safety of tocilizumab intravenous versus subcutaneous (SC) in 109 Takayasu arteritis (TAK) patients.Methods We conducted a retrospective multicentre study in referral centres from France, Italy, Spain, Armenia, Israel, Japan, Tunisia and Russia regarding biological-targeted therapies in TAK, since January 2017 to September 2019.Results A total of 109 TAK patients received at least 3 months tocilizumab therapy and were included in this study. Among them, 91 and 18 patients received intravenous and SC tocilizumab, respectively. A complete response (NIH <2 with less than 7.5 mg/day of prednisone) at 6 months was evidenced in 69% of TAK patients, of whom 57 (70%) and 11 (69%) patients were on intravenous and SC tocilizumab, respectively (p=0.95). The factors associated with complete response to tocilizumab at 6 months in multivariate analysis, only age <30 years (OR 2.85, 95% CI 1.14 to 7.12; p=0.027) and time between TAK diagnosis and tocilizumab initiation (OR 1.18, 95% CI 1.02 to 1.36; p=0.034). During the median follow-up of 30.1 months (0.4; 105.8) and 10.8 (0.1; 46.4) (p<0.0001) in patients who received tocilizumab in intravenous and SC forms, respectively, the risk of relapse was significantly higher in TAK patients on SC tocilizumab (HR=2.55, 95% CI 1.08 to 6.02; p=0.033). The overall cumulative incidence of relapse at 12 months in TAK patients was at 13.7% (95% CI 7.6% to 21.5%), with 10.3% (95% CI 4.8% to 18.4%) for those on intravenous tocilizumab vs 30.9% (95% CI 10.5% to 54.2%) for patients receiving SC tocilizumab. Adverse events occurred in 14 (15%) patients on intravenous route and in 2 (11%) on SC tocilizumab.Conclusion In this study, we confirm that tocilizumab is effective in TAK, with complete remission being achieving by 70% of disease-modifying antirheumatic drugs-refractory TAK patients at 6 months.